Functional Microbial Pigments Isolated from Chryseobacterium and Deinococcus species for Bio-paint Application - Park, Seo A.; Ahn, Soo Yeon; Choi, Kwon Young (Biotechnology and Bioprocess Engineering, 2020)
In this study, bioproduction and application of a microbial pigment from Chryseobacterium and Deinococcus species screened from soil were investigated. The pigments extracted from both cell cultures were identified as a flexirubin (FL)- and deinoxanthin-type (DX). The isolated pigments showed a mass value of 618.48 and 584.41 m/z by LC/MS, respectively. Flask production of the crude FL pigment in complex medium yielded 0.443 ± 0.047 g/L, while crude DX production was less than 20 mg/L. Similar to previously identified FL and DX pigments, both have unsaturated long-chain alkyl-substituted phenol and cyclo-hexanone units and showed excellent radical scavenging capacities of 0.6 and 3.2 mg/mL IC50 values, respectively. In order to utilize the pigments for functional painting materials, both pigments were mixed with casein paint to prepare FL bio-paint and DX bio-paint, respectively. Interestingly, yellow-colored FL bio-paint and red-colored DX bio-paint showed an outstanding coloration and coating performance onto glass plate. Furthermore, it was confirmed that the produced DX bio-paint had a unique crystal structure when analyzed by SEM.
Keywords: Bio-production; Chryseobacterium; Coating performance; Complex medium; Glass plate; Paint applications; Radical scavenging capacities; Substituted phenol; bio-paints; Chryseobacterium species; Deinococcus species; deinoxanthin; flexirubin